GAYA BAHASA RETORIS DAN KIASAN NAJWA SHIHAB DALAM GELAR WICARA MATA NAJWA DI TRANS7 - Febriani, Succy; Emidar, Emidar (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
ABSTRACT This study aims to describe the Najwa Shihab's speech style in Mata Najwa talkshow on Trans7. This type of research is qualitative with descriptive methods. The research data is in the form of quotations containing speech style. Data collection is done by searching and downloading audio-visual recordings of Mata Najwa talkshow in the website (www.youtube.com). The method used is the method of referring to tapping techniques. Data analysis is done by identifying data, giving signs and data code, classifying data using identification and classification tables, interpreting data, making conclusions. Based on the results of the study, it can be concluded that there are 173 speech styles consisting of 4 styles of Alliterative, 9 styles of asonance, 1 style of apophasis, 2 styles of apostrophe, 3 styles of asindeton, 3 polisidenton, 1  chiasmus, 7 elliptical, 8 euphemism, 4 tautology, 8 pleonasm, 2 periphasis, 3 prolepsis, 34 erotesis, 1 correction, 2 hyperbolic, 15 metaphor, 1 allegory, 10 personification, 1 allusion, 1 eponymous, 4 synekdoke, 7 meteorological, 3 antonomasia, 1 hypalase, 16 irony, 20 cynicism, 2 sarcasm. The dominant of speech style used is erotesis or rhetorical question, while the dominant of speech style used is cynicism. The use of the speech style aims to help Najwa Shihab in expressing his ideas and emotions so that use of language raises certain connotations and aesthetic values to both the speech partners and viewers of the Mata Najwa talkshow. Kata kunci: Gaya Bahasa Retoris, Kiasan, Najwa Shihab